Tracking short-term biodistribution and long-term clearance of SPIO tracers in magnetic particle imaging. (5th April 2017) - Keselman, Paul; Yu, Elaine Y; Zhou, Xinyi Y; Goodwill, Patrick W; Chandrasekharan, Prashant; Ferguson, R Matthew; Khandhar, Amit P; Kemp, Scott J; Krishnan, Kannan M; Zheng, Bo; Conolly, Steven M
Abstract: Magnetic particle imaging (MPI) is an emerging tracer-based medical imaging modality that images non-radioactive, kidney-safe superparamagnetic iron oxide (SPIO) tracers. MPI offers quantitative, high-contrast and high-SNR images, so MPI has exceptional promise for applications such as cell tracking, angiography, brain perfusion, cancer detection, traumatic brain injury and pulmonary imaging. In assessing MPI's utility for applications mentioned above, it is important to be able to assess tracer short-term biodistribution as well as long-term clearance from the body. Here, we describe the biodistribution and clearance for two commonly used tracers in MPI: Ferucarbotran (Meito Sangyo Co., Japan) and LS-oo8 (LodeSpin Labs, Seattle, WA). We successfully demonstrate that 3D MPI is able to quantitatively assess short-term biodistribution, as well as long-term tracking and clearance of these tracers in vivo .